Nothing Special   »   [go: up one dir, main page]

Trigo 2

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

Trigonometry

Reciprocal Identities Half Angle Formulas


1 1 1
cscθ = sinθ = θ 1-cosθ sin²θ = (1-cos(2θ))
sinθ cscθ sin =±√ 2
1 1 2 2
secθ = cosθ =
Right Triangle Definition cosθ secθ 1
1 1 θ 1+cosθ cos²θ = (1+cos(2θ))
For this definition we assume that 0<θ cos =±√ 2
π cotθ = tanθ = 2 2
< 2 or 0°< θ <90° tanθ cotθ
1-cos(2θ)
Pythagorean Identities θ 1-cosθ tan²θ =
tan =±√ 1+ cos (2θ)
sin²θ + cos²θ = 1 2 1+cosθ
tan²θ + 1 = sec² θ
1 + cot²θ = csc²θ Sum and Difference Formulas
sin(α±β) = sinαcosβ±cosαsinβ
Even/Odd Formulas cos(α±β) = cosαcosβ∓sinαsinβ
opposite hypotenuse sin(-θ) = -sinθ csc(-θ) = -cscθ tan α ± tan β
sinθ = cscθ = tan(α±β) =
hypotenuse opposite cos(-θ) = cosθ sec(-θ) = secθ 1∓ tan α tan β
adjacent hypotenuse
cosθ = secθ = tan(-θ) = -tanθ cot(-θ) = -cotθ
hypotenuse adjacent Product to Sum Formulas
opposite adjacent 1
tanθ = cotθ = Periodic Formulas
adjacent opposite sinαsinβ= [cos(α-β)-cos(α+β)]
If n is an integer. 2
sin(θ+2πn) = sinθ csc(θ+2πn) = cscθ 1
Unit circle definition cosαcosβ= [cos(α-β)+cos(α+β)]
cos(θ+2πn) = cosθ sec(θ+2πn) = secθ 2
For this definition θ is any angle. 1
tan(θ+πn) = tanθ cot(θ+πn) = cotθ sinαcosβ= [sin(α+β)+sin(α-β)]
2
Double Angle Formulas 1
cosαsinβ= [sin(α+β)-sin(α-β)]
sin(2θ) = 2sinθcosθ 2
cos(2θ) = cos²θ-sin²θ
Cofunction Formulas
= 2cos²θ-1 π π
=1-2sin²θ sin ( -θ) = cosθ cos ( -θ) = sinθ
2 2
2tanθ π π
y 1 tan(2θ)= csc ( -θ) = secθ sec ( -θ) = cscθ
sinθ = =1 cscθ = 1-tan²θ 2 2
1 y π π
x 1 tan ( -θ) = cotθ cot ( -θ) = tanθ
cosθ = = 1 secθ = Degrees to Radians Formulas 2 2
1 x
y x If x is an angle in degrees and t is an
tanθ = cotθ = angle in radians then
x y
π t πx 180t
= ⇒ t= and x =
180 x 180 π

Definition
y=sin-1x is equivalent to x=siny
y=cos-1x is equivalent to x=cosy
Tangent and Cotangent Identities
sinθ cosθ y=tan-1x is equivalent to x=tany
tanθ = cotθ =
cosθ sinθ
Domain and Range Law of Tangents
Function Domain Range 1
π π a-b tan 2 (α-β)
Y=sin-1x -1≤ x ≤1 - ≤y≤ =
2 2 a+b tan 1 (α+β)
Y=cos-1x -1≤ x ≤1 0≤ y ≤π 2
Y=tan-1x -∞≤ x π π 1
- ≤y≤ b-c tan 2 (β-γ)
≤∞ 2 2 =
b+c tan 1 (β+γ)
2
Inverse Properties 1
cos(cos-1(x)) = x cos-1(cos(θ)) = θ a-c tan 2 (α-γ)
=
sin(sin-1(x)) = x sin-1(sin(θ)) = θ a+c tan 1 (α+γ)
Law of Sines 2
tan(tan-1(x)) =x tan-1(tan(θ)) = θ sinα sinβ sinγ
= =
a b c Mollweide’s Formula
Alternate Notation 1
sin-1x = arcsinx a+b cos 2 (α-β)
Law of Cosines =
cos-1x = arccosx a2=b2+c2-2bccosα c 1
sin γ
tan-1x = arctanx 2
b2=a2+c2-2accosβ
c2=a2+b2-2abcos𝛾

For any ordered pair on the unit circle ( x y, ) : cosθ= x and sinθ = y

You might also like